The collected scientific papers of Paul A. Samuelson - Merton, Robert C. (Cambridge, Mass. : M.I.T. Press, 1972)
The third volume contains seventy-eight chapters representing all the scientific papers written by Paul A. Samuelson. The articles are arranged by subject in nineteen parts, and they are grouped within each part by their relationship to one another. The nineteenth contains his first contributions to the theories of portfolio selection, warrant pricing, and speculative markets under uncertainty.
Volume III
Vol. 2 edited by R.C. Merton; vol. 4 edited by H. Nagatani and K. Crowley; vol. 5 edited by Kate Crowley; vol. 6 edited by Janice Murray.
Include Bibliographical references
aia 17/11/2017
Loans
Keywords: Economics -- Collected works